Molecular Regulation of Autophagy and Asymmetric Cell Division by Cancer Stem Cell Marker CD133 - Hideki Izumi; Yasuhiko Kaneko; Akira Nakagawara (Cells, 2023)
CD133, also called prominin-1, is widely known as a cancer stem cell marker, and its high expression correlates with a poor prognosis in many cancers. CD133 was originally discovered as a plasma membranous protein in stem/progenitor cells. It is now known that Src family kinases phosphorylate the C-terminal of CD133. However, when Src kinase activity is low, CD133 is not phosphorylated by Src and is preferentially downregulated into cells through endocytosis. Endosomal CD133 then associates with HDAC6, thereby recruiting it to the centrosome via dynein motors. Thus, CD133 protein is now known to localize to the centrosome as endosomes as well as to the plasma membrane. More recently, a mechanism to explain the involvement of CD133 endosomes in asymmetric cell division was reported. Here, we would like to introduce the relationship between autophagy regulation and asymmetric cell division mediated by CD133 endosomes.